MENGGAGAS PENGAWASAN ASIMETRIS: Pendewasaan Demokrasi Melalui Model Pengawasan Asimetris (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
The General Election Supervisory Agency (Bawaslu) plays a crucial role, not only functioning as a partner of the General Election Commission (KPU) in carrying out general elections (Pemilu) but also based on Law (UU) no 17 of 2017 has a role in encouraging oversight participatory elections. This law shows that Bawaslu has a function to promote the improvement of the quality of substantive democracy in Indonesia. This article tries to answer one simple question: what supervision model can position Bawaslu as a catalyst for strengthening democracy? This article uses a qualitative approach, and based on document studies, this article argues that an asymmetric perspective is needed to implement oversight in elections. This asymmetrical model will enable the maturation of democracy to run simultaneously with discretionary space in various implementations, especially focusing on the active participation of citizens. The risk mitigation model compiled in the Election Vulnerability Index (IKP) does not cover this.
Keywords: Asymmetrical Monitoring, Democracy, Participation